(untitled) (Research, Society and Development, 2024)
Introduction: Medical knowledge is constantly evolving. The retention of information, aiming for long-term maintenance, is essential, but many are not aware of or have difficulties in applying efficient study techniques. The practice of active retrieval can improve learning, but students often do not use it effectively. Objective: This study aims to evaluate the knowledge and use of active study techniques by medical students at a University Center in Ceará. Material and methods: A quantitative observational cross-sectional study was conducted from March to June 2023, with students from the first four years of a Medicine course at a University Center in the state of Ceará. In addition to demographic data, there were questions related to the use of active study methods and their perceived efficiency. The project was approved by the Research Ethics Committee of the Institution. Results: 379 responses were analyzed. Most were in the fifth to seventh semesters (53.8%). Approximately 72% were familiar with active study methods, but 51.5% had not received guidance on the subject during their graduation. The most and least used study techniques were identified, and students preferred to use passive study techniques. Conclusion: There is a disconnect between the use of active and passive study techniques. Many still adopt less efficient approaches (passive techniques) and lack knowledge about active methods. Understanding active retrieval in medical education could allow for greater retention of knowledge by students.